Gereja Cyber-Net: Sebuah Usulan Gagasan terhadap Natur Gereja pada Revolusi Industri 4.0 dan Pascapandemi COVID-19 - Adrianus Yosia (Veritas : Jurnal Teologi dan Pelayanan, 2022)
The COVID-19 pandemic, which has been striking Indonesia for two years, has brought significant changes in society. One significant change is the amplification of digitalization and the use of the internet in everyday life. Thus, smartphones or other related technologies are becoming more common in the Industrial Revolution 4.0 context. The Church, as the fellowship of God’s people who live in the context of the digital network and smartphones, is now influenced by such a context. This article thus proposes the idea of a cyber-net church as an ontological reality of God’s people, especially in the Indonesian context. Using the approach of constructive theology, this article combines insights from networked theology (ala Heidi Campbell and Stephen Garner) and cyborg theology (ala Ilia Delio) as dialogue partners to explicate the reality of such a Church. There are three main ideas proposed in this article: (1) the cyber-net church as a third space beyond the analog versus digital nature; (2) the cyber-net church as a contextualized way of being in the world today; (3) the cyber-net church as a preparatory space for the virtual reality which is anticipated to dominate the Indonesian society in the near future.